PROBLEMS OF THE STADIAL ANALYSIS AND DEVELOPMENT OF LITHOLOGY - Kholodov V.N. (My University, 2004)
History of the evolution of concepts concerning stages of sedimentary rock formation is reviewed to show the conditional character of stadial boundaries and unreasonableness of their detailed subdivision. An insufficient knowledge of continental diagenesis is stressed and some problems of catagenesis are discussed. It is shown that metagenesis is irrelevant to the notion of sediment transformation stages and includes many purely geological processes. A rational succession of main stages of sedimentary rock formation is proposed. The main purpose of stadial analysis is shown to be the study of succession and mechanisms of mineral formation at different stages of sedimentary rock formation.